FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA PADA SANTRI PONDOK PESANTREN FADLUN MINALLOH YOGYAKARTA - Mudita Sri Hidayah (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2018)
Background: Problems of malnutrition were found in developing countries, one of them was anemia. The highest proportion of anemia in Indonesia in pregnant women was 37,1%, followed by underfives 12-59 month was 28,1% and population ≥1 year was 21,7%. Adolescents also become susceptible to anemia. Anemia can lead to fatigue, disturbed concentration resulting in decreased learning achievement and work productivity, resulting in a weak immune system that causes infection easily. The purpose of this research is to know the frequency distribution of anemia occurrence at students of Fadlun Minalloh Boarding School. Methods: The study used cross-sectional design with 43 female students at Fadlun Minalloh boarding school. Hemoglobin levels were measured using the Hemo-Cue system, weight measured using digital scales and height using microtoise. Body image and breakfast habits were measured using questionnaire. Chi Square test was used for bivariate. Result: The percentage of anemia in PP Fadlun Minalloh was 58,3%. Anemia is most prevalent in v the 12-14 years age group of 44%. Most santri have breakfast habits of 88.4%. Most santri have good nutrition status that is equal to 48,9%. Most of the respondents had a positive body image of 60.5%. The results of the bivariate analysis showed no significant relationship between age (p =0,14), BMI (0,85), body image (0,94) and breakfast habits(0,93) with anemia in female students.  Conclution: More than 50% of female students at Fadlun Minalloh boarding school were anemia.The greatest incidence of anemia in the 12-14 year age group. Most respondents have breakfast habits, good nutritional status, and positive body image. There was no significant relationship between age, BMI, body image, breakfast habits with the incidence of anemia on adolescent girls. Keywords: anemia, body image, BMI